Epirus Revisited. New Perceptions of its History and Material Culture - Stavrakos, Christos (Brepols, 2020)
The opening of the borders of Albania in the 1990s stimulated an increased interest in its cultural heritage and led to extensive research, as well as archaeological investigations. These, however, have mainly concentrated within Albania's present-day borders and have lacked broader contextualization. Very recent excavations in Greece, which resulted from the construction of the new Ionia Odos highway, have, however brought to light unexpected and interesting material that changes our image of the monumental topography and the settlements in Epirus. New studies concerning Epirus and its broader connections during the early and later Ottoman periods provide a broader impression of the region and its relationships with the large economic centres of the West, as well as with the spiritual-religious and political centres of the Balkans.